2013
DOI: 10.4236/jct.2013.46a1002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activities and Interaction of Imiquimod and Flex-Het, SHetA2, in Melanoma and Ovarian Cancer

Abstract: New strategies are needed to treat cancers that do not respond to chemotherapy or resist chemotherapy after responding initially. The objective of this study was to evaluate non-cytotoxic drugs against two of these cancers, melanoma and ovarian cancer. Imiquimod is an immune stimulant that induces apoptosis in cancer cells. Flexible-Heteroarotinoids (Flex-Hets) are small molecules that regulate growth, differentiation and apoptosis in cancer cells with reduced effects on normal cells. Both imiquimod and SHetA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The levels of cyclin D1 in tissues were evaluated as pharmacodynamic end point to confirm if SHetA2 concentrations in tissue were indeed able to induce an effect at tissue level 9 . SHetA2 induces phosphorylation, ubiquitination and proteasomal degradation of cyclin D1 that leads to G1 cell cycle arrest in multiple cancer cell lines 6, 18, 52 . It is also reported that, as cervical dysplasia progresses to invasive cancer, the expression of cyclin D1 increases.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of cyclin D1 in tissues were evaluated as pharmacodynamic end point to confirm if SHetA2 concentrations in tissue were indeed able to induce an effect at tissue level 9 . SHetA2 induces phosphorylation, ubiquitination and proteasomal degradation of cyclin D1 that leads to G1 cell cycle arrest in multiple cancer cell lines 6, 18, 52 . It is also reported that, as cervical dysplasia progresses to invasive cancer, the expression of cyclin D1 increases.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical testing for our lead compound, a flexible heteroarotinoid (Flex-Het) called Sulfur Het A2 (SHetA2, NSC721689) demonstrated reasonable pharmacokinetics and lack of mutagenicity, carcinogenicity, teratogenicity and toxicity [ 1 5 ]. SHetA2 has a wide therapeutic window as indicated by the No Observed Adverse Effect Level (NOAEL) of >1,500 mg/kg/day identified in the 28 day dog toxicity model in comparison to the ability of 10 to 60 mg/kg/day to inhibit xenograft tumor growth [ 5 8 ]. This lack of in vivo toxicity, along with oral bioavailability and documented inhibition of colorectal tumorigenesis in the APC min/+ mouse model at 30 mg/kg given 5 days per week, make SHetA2 an ideal candidate for a cancer prevention drug [ 9 ].…”
Section: Introductionmentioning
confidence: 99%